Solving a System of Linear Equations Based on Z-Numbers to Determinate the Market Balance Value - Zeinab Motamedi Pour; Tofigh Allahviranloo; Mozhdeh Afshar Kermani; Saeid Abbasbandy (Advances in Fuzzy Systems)
In this article, a general linear equations system with Z-number’s data is introduced. Since the nature of Z-numbers has two parameters, namely, reliability and fuzziness, it is difficult to find the exact solution to these systems. Therefore, a numerical procedure for calculating the solution is designed. The proposed method is illustrated with some applied examples. Determining the value of the market balance is one of the examined examples.